2018
DOI: 10.1074/jbc.ra118.004617
|View full text |Cite
|
Sign up to set email alerts
|

β-Cell mass restoration by α7 nicotinic acetylcholine receptor activation

Abstract: Edited by Jeffrey E. PessinAlthough it is well-established how nutrients, growth factors, and hormones impact functional ␤-cell mass (BCM), the influence of the central nervous system in this regard, and especially in the context of islet immune modulation, has been understudied. Here we investigated the expression and activity of pancreatic islet ␣7 nicotinic acetylcholine receptor (␣7nAChR) in islet anti-inflammatory and prosurvival signaling. Systemic administration of ␣7nAChR agonists in mice improved gluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 45 publications
(70 reference statements)
3
18
4
Order By: Relevance
“…One of the reasons for the conflicting observations of the effect of nicotine on UPR might be related to the tissue specificity of the effect of nicotine. In β‐cells, previous studies showed the expressions of the α7 subunit in rat islet β‐cells, and the α2, α3, α4, α7 and β2 subunits in INS‐1 cells. We also preliminarily confirmed the expression of the α2, α5 and β2 subunits, as well as the α7 subunit (Figure ; Table ).…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…One of the reasons for the conflicting observations of the effect of nicotine on UPR might be related to the tissue specificity of the effect of nicotine. In β‐cells, previous studies showed the expressions of the α7 subunit in rat islet β‐cells, and the α2, α3, α4, α7 and β2 subunits in INS‐1 cells. We also preliminarily confirmed the expression of the α2, α5 and β2 subunits, as well as the α7 subunit (Figure ; Table ).…”
Section: Discussionsupporting
confidence: 77%
“…It has also been shown that nicotine or the systemic increase in ACh levels ameliorates the diabetic phenotypes by stimulating the Th1 to Th2 cytokine switch or pancreatic T‐cell differentiation in NOD mice and multiple low‐dose streptozotocin mice. In addition, the specific stimulation of nAChR α7 has recently been shown to activate anti‐inflammatory and prosurvival pathways in cytokine‐treated INS‐1 cells and murine islets. In contrast, we and other groups have recently shown that UPR markers are induced in β‐cells from type 1 diabetes patients and NOD mice, and that established diabetes in NOD mice could be reversed by KIRA.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Previously, we showed that the brain α7 and α4β2 nAChRs could be restored if LPS-treated mice were injected with mesenchymal stem cells (MSCs) or their conditioned medium (Lykhmus et al, 2019a). The α7 nAChRs are known to mediate pro-survival signaling (Smedlund et al, 2011;Gupta et al, 2018); therefore, their activation could in some way resemble the effect of the growth/trophic factors produced by MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…We thus postulate that cynandione A stimulates β-endorphin expression through autocrime IL-10 expression via the STAT3 signaling. Activation of α7 nAChRs indeed led to reducing in ammatory drive through a JAK2-STAT3 pathway that couples with CREB/Irs2/Akt survival signaling in the mouse islets [73]. α7 nAChR activation increased hypothalamic POMC expression by triggering JAK2/STAT3 pathway [74].…”
Section: Cynandione a Stimulated Il-10 And β-Endorphin Expression In mentioning
confidence: 99%